Epigenetic profile in chronic lymphocytic leukemia using methylation-specific multiplex ligation-dependent probe amplification. (October 2012) - Cosialls, Ana M; Santidrián, Antonio F; Coll-Mulet, Llorenç; Iglesias-Serret, Daniel; González-Gironès, Diana M; Pérez-Perarnau, Alba; Rubio-Patiño, Camila; González-Barca, Eva; Alonso, Esther; Pons, Gabriel; Gil, Joan
Aim: To analyze the methylation status of 35 tumor suppressor genes using methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in chronic lymphocytic leukemia (CLL).Materials & methods: The DNA of 37 samples from patients with CLL, six healthy donors, and Jurkat and Ramos cell lines was analyzed by MS-MLPA.Results: Our results confirm that hypermethylation is a common and not randomly distributed event in CLL, and some genes, such as WT1, CDH13, IGSF4/TSLC1, GATA5, DAPK1 and RARB, are hypermethylated in more than 25% of the analyzed samples. Importantly, MS-MLPA also detected hypermethylation of some genes not reported previously in CLL, and their methylation status was confirmed by bisulfite sequencing.Conclusion: These results indicate that MS-MLPA is a useful technique for the detection of methylation in CLL samples. Selecting CLL-specific methylation targets in order to generate a CLL-specific MS-MLPA probe set could enhance its usefulness as a tool in studies of risk stratification and guiding the best therapeutic decision.